To address surface reaction network complexity using scaling relations machine learning and DFT calculations - Zachary W. Ulissi (Nature Portfolio, 2017)
Finding catalyst mechanisms remains a challenge due to the complexity of hydrocarbon chemistry. Here, the authors shows that scaling relations and machine-learning methods can focus full-accuracy methods on the small subset of rate-limiting reactions allowing larger reaction networks to be treated.